2018
DOI: 10.3413/nukmed-0964-18-03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sialendoscopy on improving health related quality of life in patients suffering from radioiodineinduced xerostomia

Abstract: Summary Introduction: Xerostomia following radioiodine therapy (RIT) in patients suffering from differentiated thyroid cancer is a common side effect in 2 % to 67 % of patients treated with radioiodine (I-131). In order to evaluate the impact of sialendoscopy on health related quality of life (HRQOL) in patients suffering from therapy induced sialadenitis and xerostomia, we analyzed findings from two dedicated questionnaires (Xerostomy Questionnaire XQ and Xerostomy Inventory XI) in patients before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Self-reported health assessment is gaining importance in medical research in recent years and is frequently chosen as a primary endpoint in studies, highlighting the focus on patient's individual impairment (Bhayani et al, 2015;Brettschneider et al, 2011;Eisbruch et al, 2003;Rathke et al, 2019). Studies have shown that objective endpoints of studies such as scintigraphy, with regard to xerostomia, are not always congruent with subjective measurements (Bulut et al, 2018;Eisbruch et al, 2003;Rathke et al, 2019). Therefore, self-report assessments of oral health and functional status are more frequently utilized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported health assessment is gaining importance in medical research in recent years and is frequently chosen as a primary endpoint in studies, highlighting the focus on patient's individual impairment (Bhayani et al, 2015;Brettschneider et al, 2011;Eisbruch et al, 2003;Rathke et al, 2019). Studies have shown that objective endpoints of studies such as scintigraphy, with regard to xerostomia, are not always congruent with subjective measurements (Bulut et al, 2018;Eisbruch et al, 2003;Rathke et al, 2019). Therefore, self-report assessments of oral health and functional status are more frequently utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen patients underwent the sialendoscopy procedure, all by the same surgeon (OCB). The procedure was performed under local anesthesia using a standard approach as described in the literature (Bulut et al, 2018;Rathke et al, 2019). Three patients received additional sialendoscopies as each cycle of Lu-PSMA had worsened their xerostomia resulting in 23 pre-and postoperative assessments.…”
Section: Patientsmentioning
confidence: 99%
“…6,7 Sialendoscopy is a novel means for alleviating obstructive symptoms of RAI-induced sialadenitis 10 and improving the quality of life of affected patients. 8 Recent studies have shown promising outcomes when the procedure is performed early in the course of the disease. 11 The present study aimed to evaluate the early ultrasonographic features of the major salivary glands following postoperative RAI in patients with PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Secondarily, soft‐tissue neck ultrasound can help clinicians evaluate the salivary glands. It can detect diffuse and focal lesions, dilated ducts, areas of calcification, and stones within the parotid glands 8 . In a study investigating the prevalence of ultrasound‐detected sialadenitis caused by external beam radiotherapy, Horvath et al 9 found changes in the echotexture, echogenicity, and margins of the major salivary glands and reduced glandular size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation